SPELLING ERRORS IN STUDENT SCIENTIFIC WORKS - Tyasmiarni Citrawati; Agung Setyawan (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to describe spelling errors in student scientific works. The errors studied included the use of letters, writing words, using punctuation marks, and writing absorption elements. The instrument used is a human instrument. The data was taken from spelling errors in the scientific work of students Trunojoyo Madura University Primary School Teacher Education (PGSD) in the form of background papers. The results showed that there were 156 errors. The spelling errors which include the use of letter as many as 70 errors, writing in as a prefix or preposition 43 errors, writing punctuation 40 errors, and writing absorption elements as many as 3 errors. This shows that students still lac understanding of spelling in scientific writing and need intensive guidance both in theory and application.